2013
DOI: 10.1002/ajmg.a.35762
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of a frontonasal phenotype caused by a novel ALX4 mutation

Abstract: Frontonasal dysplasias (FND) comprise a spectrum of disorders caused by abnormal median facial development. Its etiology is still poorly understood but recently frontonasal dysplasia phenotypes were linked to loss-of-function mutations in the ALX homeobox gene family, which comprises the ALX1, ALX3, and ALX4 genes. All ALX-related frontonasal phenotypes till date had been compatible with an autosomal recessive mode of inheritance. In contrast, heterozygous loss-of-function mutations in ALX4 had been only assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 14 publications
4
22
0
2
Order By: Relevance
“…Homozygous mutations in alx 1 are associated with profound frontonasal dysplasia and microophthalmia in humans (Bertola et al, 2013; Uz et al, 2010), and zebrafish alx1 morphants develop with hypoplastic craniofacial cartilages and coloboma (Dee et al, 2013). WISH analysis corroborated depletion of alx1 transcript in zic2 mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homozygous mutations in alx 1 are associated with profound frontonasal dysplasia and microophthalmia in humans (Bertola et al, 2013; Uz et al, 2010), and zebrafish alx1 morphants develop with hypoplastic craniofacial cartilages and coloboma (Dee et al, 2013). WISH analysis corroborated depletion of alx1 transcript in zic2 mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zebrafish zic2a and zic2b are predominantly expressed in the presumptive neural crest (Grinblat and Sive, 2001; Nyholm et al, 2007; Teslaa et al, 2013; Toyama et al, 2004); hence it is tempting to speculate that zic2 controls ventral retinal morphogenesis indirectly, via a primary function in neural crest. Alx1 is an attractive candidate effector of Zic2, since alx gene family members function in periocular neural crest to regulate retinal morphogenesis in human, mouse and zebrafish (Bertola et al, 2013; Dee et al, 2013; Lakhwani et al, 2010; Qu et al, 1999; Uz et al, 2010; Zhao et al, 1996). …”
Section: Discussionmentioning
confidence: 99%
“…FND2 results from homozygous ALX4 mutations and has been documented in 3 consanguineous families [Kayserili et al, 2009;Kariminejad et al, 2014]. Interestingly, heterozygous mutations in ALX4 cause parietal foramina 2 (OMIM 609597) which, in severe cases, may include hypertelorism and nasal abnormalities [Wuyts et al, 2000;Mavrogiannis et al, 2001;Kayserili et al, 2012;Bertola et al, 2013;Altunoglu et al, 2014]. Parietal foramina 1 (OMIM 168500) is caused by a heterozygous mutation in the MSX2 gene [Wilkie et al, 2000;Spruijt et al, 2005] and parietal foramina 1 and 2 are clinically indistinguishable [Mavrogiannis et al, 2006].…”
Section: Phenotypic Spectrum Of the Fndsmentioning
confidence: 99%
“…Clinical features associated with both genes were known to be similar, without overt genotype–phenotype correlations, but with marked inter‐ and intrafamilial variability in expression . Recently it was reported that PFM patients with ALX4 mutations may present with mild features of frontonasal dysplasia, including mild hypertelorism and alar notching …”
mentioning
confidence: 99%
“…6 Recently it was reported that PFM patients with ALX4 mutations may present with mild features of frontonasal dysplasia, including mild hypertelorism and alar notching. 7,8 A 35-year-old G2P1L1 woman was referred to the tertiary prenatal diagnosis center at 20 weeks of gestation, because of 'pathological ultrasound findings suggestive for encephalocele'. Ultrasonography revealed bilateral calvarial defects of 17 × 19 mm in size at parietal bones, close to the intersection of sagittal and lambdoid sutures.…”
mentioning
confidence: 99%